Causes of Contractor's Business Failure in Developing Countries: The Case of Palestine - Enshassi, Adnan; Al-Hallaq, Khalid; Mohamed, Sherif (Penerbit Universiti Sains Malaysia, 2006)
The construction industry has unique characteristics that sharply distinguish it from other sectors of the economy. It is fragmented, very sensitive to the economic cycles and political environment, and has a significantly high rate of business failure. Business failure, collapse and bankruptcy are common terms in the industry due to the many risks inherited in how the industry operates. Throughout the world, the relative ease of entry gives rise to a large number of contracting firms competing fiercely in the market exposing many of them to business failure, Palestine is no exception. The objectives of this paper are to report on a research study which aims at exploring the causes of contractor's business failure in Palestine, and investigating their severity from the contractor's point of view. The study's results shows that the main causes of business failure are delay in collecting debt from clients (donors), border closure, heavy dependence on bank loans and payment of high interest on these loans, lack of capital, absence of industry regulations, low profit margin due to high competition, awarding contracts by client to the lowest bidder, and lack of experience in contract management. Based on these findings, recommendations to the Palestinian National Authority (PNA) and local contractors are presented in this paper.